Co‐flow injection for serial crystallography at X‐ray free‐electron lasers. Issue 1 (16th December 2021) - Doppler, Diandra; Rabbani, Mohammad T.; Letrun, Romain; Cruz Villarreal, Jorvani; Kim, Dai Hyun; Gandhi, Sahir; Egatz-Gomez, Ana; Sonker, Mukul; Chen, Joe; Koua, Faisal H. M.; Yang, Jayhow; Youssef, Mohamed; et al.
Abstract : The development and characterization are described of a co‐flow injector for liquid‐jet crystal delivery applied for serial crystallography with X‐ray free‐electron lasers. Abstract : Serial femtosecond crystallography (SFX) is a powerful technique that exploits X‐ray free‐electron lasers to determine the structure of macromolecules at room temperature. Despite the impressive exposition of structural details with this novel crystallographic approach, the methods currently available to introduce crystals into the path of the X‐ray beam sometimes exhibit serious drawbacks. Samples requiring liquid injection of crystal slurries consume large quantities of crystals (at times up to a gram of protein per data set), may not be compatible with vacuum configurations on beamlines or provide a high background due to additional sheathing liquids present during the injection. Proposed and characterized here is the use of an immiscible inert oil phase to supplement the flow of sample in a hybrid microfluidic 3D‐printed co‐flow device. Co‐flow generation is reported with sample and oil phases flowing in parallel, resulting in stable injection conditions for two different resin materials experimentally. A numerical model is presented that adequately predicts these flow‐rate conditions. The co‐flow generating devices reduce crystal clogging effects, have the potential to conserve protein crystal samples up to 95% and will allow degradation‐free light‐induced time‐resolved SFX.